2018
DOI: 10.1155/2018/4783214
|View full text |Cite
|
Sign up to set email alerts
|

Investor Sentiment and the Basis of CSI 300 Stock Index Futures: An Empirical Study Based on QVAR Model and Quantile Regression

Abstract: The asymmetrical mutual influence of investor sentiment and the basis of CSI 300 stock index futures under conditions in different market situations was investigated using the quantile vector autoregressive model (QVAR). The article also discussed asymmetrical influence of investor sentiment on the basis under conditions in different investor structures using the quantile regression method. On this basis, we obtained several important conclusions: (1) There exists a one-way causal relationship where investor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…It is not surprising, therefore, that the effect of investor sentiment on stock returns has been the focus of increased theoretical and empirical investigation in behavioral finance literature focusing on three elementary units, namely limits to arbitrage (e.g., [1]), investors' behavioral preferences (see, [2]), and their sentiment [3][4][5][6]. Investor sentiment is defined as the conception that depicts in what ways investors develop their preferences and beliefs using moods, emotions, psychological bias, and cognitive bias; and afterward forecast future asset prices.…”
Section: Introductionmentioning
confidence: 99%
“…It is not surprising, therefore, that the effect of investor sentiment on stock returns has been the focus of increased theoretical and empirical investigation in behavioral finance literature focusing on three elementary units, namely limits to arbitrage (e.g., [1]), investors' behavioral preferences (see, [2]), and their sentiment [3][4][5][6]. Investor sentiment is defined as the conception that depicts in what ways investors develop their preferences and beliefs using moods, emotions, psychological bias, and cognitive bias; and afterward forecast future asset prices.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the impact of energy prices on investor sentiment in the United States [22] (Apergis et al, 2017) and the importance of investor sentiment in key events such as the COVID-19 pandemic, revealing its impact on investor behavior and market dynamics [23] (Song et al, 2021). In addition, it was found that investor sentiment affects trade to varying degrees under different market conditions, influencing returns and volatility [24] (Liu & An, 2018). It has been observed that investor sentiment has a stronger impact on firms in strong market competition than firms in weak market competition [25] (Huang et al, 2019).…”
Section: Research On the Impact Of Investor Sentimentmentioning
confidence: 99%
“…Our model allows us to gauge how these predictions could have panned out empirically. We use three metrics of market reaction: the Chinese market sentiment [25][26][27], returns on the Shanghai stock market, and yields on a Bank of China 10-year bond. Using our model, we can directly and relatively parsimoniously explore the conditions prevailing in dark pools, artificially supplying or denying our assumed traders any external information about the activities of their colleagues or the direction of indexes.…”
Section: Literature Reviewmentioning
confidence: 99%